Encontros afetivos em quintais urbanos: um estudo sobre famílias e sociabilidade no Subúrbio Ferroviário de Salvador (BA) - Wanderlene Cardozo Ferreira Reis; José Eduardo Ferreira Santos; Ana Cecília de Sousa B. Bastos; Giuseppina Marsico; Elaine Pedreira Rabinovich (Ciências Sociais Unisinos)
This text is part of a study whose final objective was to investigate the meanings attributed to backyards in narratives of different generations of families living in urban areas in the 21st century in the city of Salvador, Bahia. In this article, it is proposed the study of backyards as places of resistance and belongings, starting from the necessity that the subject has to build a context of affective life, associated to the place. We suggest the use of the terms "topophilia", "affectivation" and "liminaridade" as triad entities, which, when complemented, allow the understanding of the interrelations between place and family in the context of development.